2012
DOI: 10.4049/jimmunol.1103068
|View full text |Cite
|
Sign up to set email alerts
|

Dectin-1 Stimulation Induces Suppressor of Cytokine Signaling 1, Thereby Modulating TLR Signaling and T Cell Responses

Abstract: Suppressor of cytokine signaling (SOCS) proteins serve as negative regulators of cytokine receptor signaling. However, SOCS proteins are not only induced via the JAK/STAT pathway, but are also transcribed on triggering of pattern recognition receptors such as TLRs. We now show that SOCS1 can also be induced by the non-TLR pattern recognition receptor Dectin-1 in murine bone marrow-derived dendritic cells and macrophages (BMMs). The C-type lectin Dectin-1 binds to yeasts and signals either in an autonomous mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 55 publications
3
36
0
Order By: Relevance
“…The list of the significantly up-regulated genes in RBL-2H3 cells overexpressing Dectin-1 WT after 2 h of curdlan stimulation is shown in Table 1. Consistent with previous studies in macrophages and DCs, gene expressions of TNF-␣ (12, 13, 15), IL-4/IL-13 (38,39), early growth response transcription factor 3 (40,41), and suppressor of cytokine signaling 1 (42) were also up-regulated in curdlan-stimulated mast cells. Interestingly, curdlan did not stimulate gene expressions that were previously reported in macrophages and DCs, such as IL-1␤ (43, 44), IL-2 (18), [18][19][20], and IL-12 (18,20).…”
Section: Curdlan Stimulates the Expression Of Characteristic Genes Insupporting
confidence: 78%
See 1 more Smart Citation
“…The list of the significantly up-regulated genes in RBL-2H3 cells overexpressing Dectin-1 WT after 2 h of curdlan stimulation is shown in Table 1. Consistent with previous studies in macrophages and DCs, gene expressions of TNF-␣ (12, 13, 15), IL-4/IL-13 (38,39), early growth response transcription factor 3 (40,41), and suppressor of cytokine signaling 1 (42) were also up-regulated in curdlan-stimulated mast cells. Interestingly, curdlan did not stimulate gene expressions that were previously reported in macrophages and DCs, such as IL-1␤ (43, 44), IL-2 (18), [18][19][20], and IL-12 (18,20).…”
Section: Curdlan Stimulates the Expression Of Characteristic Genes Insupporting
confidence: 78%
“…With immunoblotting using IB␣, IB kinase, and phospho-IB kinase antibodies, NF-B is not activated with curdlan stimulation in RBL-2H3 cells (data not shown). Goodridge et al (63) demonstrated that although Dectin-1 signals directly activate NF-B in mouse DCs, Dectin-1 signaling alone does not activate NF-B in mouse macrophages (14,42,63). According to this, Dectin-1-mediated activation of NF-B in mast cells may not activate in the same manner as that in macrophages.…”
Section: Discussionmentioning
confidence: 98%
“…Activation of dectin-1 by C. albicans has been shown to induce interleukin 10 (IL-10), which has an inhibitory effect over TLR by targeting MyD88 (10,11). Similar studies have also shown that dampening of TLR-triggered protective immune responses is mediated by dectin-1-induced expression of suppressor of cytokine signaling 1 (SOCS-1) (12).…”
mentioning
confidence: 53%
“…It has recently been reported that the soluble form of β-glucan does not activate Dectin-1 signaling (28). Additionally, Dectin-1 signaling inhibits TLR9-mediated cytokine production through suppressor of cytokine signaling 1 induction (29). Therefore, we examined the agonistic activity of SPG.…”
Section: K3-spg Is a Prominent Vaccine Adjuvant That Induces Potent Ctlmentioning
confidence: 99%